The cartulary-chronicle of St-Pierre of Bèze - Bouchard, Constance Brittain (Medieval Academy books, 2019)
The cartulary-chronicle of the Burgundian monastery of Bèze reveals how a twelfth-century monk viewed the 500-year-long history of his house.